Classification of fruits using Probabilistic Neural Networks - Improvement using color features - Mustafa N.B.A.; Arumugam K.; Ahmed S.K.; Sharrif Z.A.Md. (2023)
This paper presents a novel approach for the development of an intelligent fruit sorting system using techniques from Digital Image Processing and Artificial Neural Networks. The aim is to develop a fast and effective classification method along with a target of 100% efficiency. Five fruits; i.e., apples, bananas, carrots, mangoes and oranges were analysed and seventeen features were extracted based on the fruits' morphological and colour characteristics. A regular digital camera was used to acquire the images, and all manipulations were performed in a MATLAB/SIMULINK environment. The results obtained were a significant improvement over a previous study. 2011 IEEE.